ANALISIS PENGELOLAAN PELABUHAN PERIKANAN BERWAWASAN LINGKUNGAN DI PELABUHAN PERIKANAN SAMUDERA NIZAM ZACHMAN JAKARTA - Supriyanto Supriyanto (Jurnal Ilmu Lingkungan, 2013)
Fishing Port of Nizam Zachman Jakarta (PPSNZJ) classified in to port of type A and thelargest port in Indonesia as well has adequate facilities. Complexity of the activity that is in PPSNZJ can affect the quality of the port environment. The problems that occur in PPSNZJare hygiene problems, environmental pollution by solid and liquid waste, waste waterdrainage is clogged and causing odor. This study aims to analyze the environmentalmanagement in PPSNZJ, analyzing the role of stakeholders in environmental management in PPSNZJ and formulate a PPSNZJ management scenarios based Eco Port. This studycontributes to science, for consideration and advice to stakeholders in the management andutilization of environmentally sustainable fishing port. The research was conducted by surveymethod and determination of respondent conducted with purposive sampling. Data analysisusing comparative analysis with the concept of Eco Port. The results showed that PPSNZJ inits management do not meet the concept of Eco Port. PPSNZJ just take notice of themanagement of social, economic and less attention to the ecological aspects. PPSNZJ environmental management must implement port scenarios that correspond to the concept ofEco Port.